Neurostimulation of the Lacrimal Nerve for Enhanced Tear Production. Issue 2 (March 2015) - Kossler, Andrea L.; Wang, Jianhua; Feuer, William; Tse, David T.
<x xml:space="preserve">Abstract</x> Purpose: To design a proof-of-concept study to assess the effect of lacrimal nerve stimulation (LNS) with an implantable pulse generator (IPG) to increase aqueous tear production. Methods: Experimental animal study design of 6 Dutch Belted rabbits. Ultra high-resolution optical coherence tomography (UHR-OCT) quantified tear production by measuring the baseline tear volume of each rabbit's OD and OS. A neurostimulator was implanted adjacent to the right lacrimal nerve. After 2 minutes of LNS (100 μs, 1.6 mA, 20 Hz, 5–8 V), the tear volumes were measured with UHR-OCT. The change in tear volume was quantified and compared with the nonstimulated OS. Three rabbits underwent chronic LNS (100 μs, 1.6 mA, 10 Hz, 2 V) and their lacrimal glands were harvested for histopathologic analysis. Results: The UHR-OCT imaging of the OD tear volume showed a 441% average increase in tear production after LNS as a percent of baseline. After stimulation, OD had statistically significant greater increase in tear volumes than OS (p = 0.028, Wilcoxon test). Poststimulation OD tear volumes were significantly greater compared with baseline (p = 0.028, Wilcoxon test). Histopathologic examination of the lacrimal glands showed no discernible tissue damage from chronic neurostimulation. In addition, there were no gross adverse effects on the general well-being of the animals due to chronic stimulation. Conclusions: LNS with an IPG appears to increase aqueous tear production. Chronic LNS showed no histopathologic lacrimal gland damage. This study suggests that LNS is a promising new treatment strategy to increase aqueous tear production.